2ab-7b-5ab-6b=

Simple and best practice solution for 2ab-7b-5ab-6b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ab-7b-5ab-6b= equation:


Simplifying
2ab + -7b + -5ab + -6b = 0

Reorder the terms:
2ab + -5ab + -7b + -6b = 0

Combine like terms: 2ab + -5ab = -3ab
-3ab + -7b + -6b = 0

Combine like terms: -7b + -6b = -13b
-3ab + -13b = 0

Solving
-3ab + -13b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '13b' to each side of the equation.
-3ab + -13b + 13b = 0 + 13b

Combine like terms: -13b + 13b = 0
-3ab + 0 = 0 + 13b
-3ab = 0 + 13b
Remove the zero:
-3ab = 13b

Divide each side by '-3b'.
a = -4.333333333

Simplifying
a = -4.333333333

See similar equations:

| 7x-8y=13 | | 3x+4+5x-6=180 | | 8-3(x+2)=7 | | 2(x-7)+4=8 | | 6=6+n | | 2+4x=5x-1 | | 15+(3x-6)=(9+x)2 | | -6.5=-4.3-n | | 5x+1-5x=8 | | x/(-6)=-14 | | x^2-28X+180=y | | (x/4)+3x/2=3/8 | | 8x-19=19+11x | | -6x+2y=-5 | | x/4+3x/2=3/8 | | -5y+21=36 | | 5(5x-2)+3=-1 | | 5x-1x=15-x | | 7(x-6)+28=-21 | | 4x+(4-4x)=4 | | x/21=-3 | | -144=-6k | | 6(6-5)+36-7= | | -1x+8=-7x+2 | | -1x+8=7x+2 | | x+3+-2=10 | | 1/2(2p+1)-(3p+2)=3/4 | | 14m+3n-4m+10n= | | -144=6k | | 6x+3=1x-12 | | 2x-3(x-1)=9 | | 6a+12=2(3a-6)+2a |

Equations solver categories